La locomotora minero energética y su impacto en el desarrollo territorial en la región del Llano (2016)
With the entry in force of the Plan National of Development (PND 2010-2014) is seeks it prosperity in it reference to them aspects social, economic and of security, with the objective of create a country in peace where dominate them low indexes of poverty, of it hand with minor levels of unemployment and a total coverage in education during the execution of the Plan national development 2010-2014.